Forum Kemitraan Polisi Masyarakat dan Pemolisian Masyarakat: Kajian Implementasi Peraturan Kepolisian RI Nomor 1 Tahun 2021 tentang Pemolisian Masyarakat - Sri Sudono Saliro; Faldini Kholdi; Yudith Evametha Vitranilla; Hamdani (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to see how effective the implementation of the Republic of Indonesia National Police Regulation Number 1 of 2021 concerning Community Policing by the Community Police Partnership Forum in Tekarang District is?, and what are the supporting and inhibiting elements in the implementation of the Regulation?. This study uses empirical law, which is a legal research method with a field research approach or factual conditions that occur in the social environment. To obtain data, researchers use observation and interview guidelines. Based on the results of the study, it was found that the application of the law to the Republic of Indonesia National Police Regulation Number 1 of 2021 concerning Community Policing by the Community Police Partnership Forum in Tekarang District has not been implemented effectively, and that the supporting factors include: the legal factor itself, law enforcement factors and community factors, while the inhibiting factor is the law enforcement factor which is only limited to the formation of the Community Police Partnership Forum (FKPM), but there is no work program. In addition, the facility factor is the absence of the Community Police Partnership Center (BKPM) and the factor of minimal public awareness and understanding of FKPM and community policing.